Physiological performance of soybean genotypes grown under irrigated and rainfed conditions - Cotrim, Mayara Fávero [UNESP]; Gava, Ricardo; Campos, Cid Naudi Silva; de David, Carlos Henrique Oliveira; Reis, Igor de Assis; Teodoro, Larissa Pereira Ribeiro; Teodoro, Paulo Eduardo [UNESP] (Wiley, 2021)
Gas exchange analysis is an important technique, as the reduction in yield may be related to the decreased photosynthetic activity, due to adverse climatic factors in the growing site. The hypothesis of this study was that contrasting soil water conditions result in different photosynthetic performance in soybean genotypes. Thus, our objective was to analyse the physiological capacity in soybean genotypes under field conditions with optimal soil moisture and under water deficit. The experimental design was random blocks with 10 genotypes (P1, P2, P3, P4, P5, P6, P7, P8, P9 and P10) and three replicates. Individual analysis of variance was performed in both environments (irrigated and rainfed), and a correlation network between the traits was generated. We measured the traits net photosynthesis, stomatal conductance, internal CO2 concentration, instant water-use efficiency, instant carboxylation efficiency and grain yield. Stressed plants reduce stomatal conductance and transpiration, but increase the instant water-use efficiency as a defence mechanism in sub-optimal soil moisture conditions. The P6 genotype obtained better physiological capacity under irrigated conditions, while the P10 genotype showed the better performance under rainfed conditions, which makes it tolerant to water stress. Our findings can contribute to the genotype formation and parental choice steps in breeding programs aimed at obtaining both irrigation-responsive and drought-tolerant genotypes.
Keywords: abiotic stress; gas exchange analysis; Glycine Max. (L) Merrill